Grapevine bioclimatic indices in relation to climate change: a case study in the Portuguese Douro Demarcated Region - Blanco-Ward, Daniel (2018)
Climate change is of major relevance to wine production as most of the wine-growing regions of the world, in particular the Douro region, are located within relatively narrow latitudinal bands with average growing season temperatures limited to 13-21ºC. This study focuses on the temporal variability of three grapevine bioclimatic indices, which are commonly used as part of the Geoviticulture Multicriteria Climatic Classification System (MCC) to classify the climate of wine producing regions worldwide. Dynamical downscaling of MPI-ESM-LR global data forced with RCP8.5 climatic scenario is performed with the Weather Research and Forecast (WRF) model to a regional scale including the Douro valley of Portugal for recent-past (1986-2005) and future periods (2046-2065; 2081-2100). Results indicate significant shifts towards warmer and dryer conditions during the growing season and higher night temperatures during the grape ripening period. An assessment on the statistical significance of the differences between the recent-past and the future scenarios and the potential impact on wine production in the study area is performed. These results will provide evidence for future strategies aimed to preserve the high-quality wines in the region and their typicality in a sustainable way.